AKURASI DAN OBJEKTIVITAS BERITA MEDIA ONLINE - Widiyawati, Wahyu (Prodi Ilmu Komunikasi Universitas Sahid Surakarta, 2018)
Online journalism is often in the spotlight because sometimes in sacrificing the basic principles of journalism such as accuracy and objectivity of news. This study describes the news accuracy and objectivity of online journalism, especially in Solopos.com. This study usescontent analysis research with mix method qualitative and quantitative. The conclusion of this study shows that as an online journalism media, Solopos.com is still accurat and objective in its news.